Improving learning motivation of broken home students by creed and morals teachers at mts - Deni Irawan; Ilham Putri Handayani; Febriana Wardiastuti (At Turots: Jurnal Pendidikan Islam, 2024)
Aqidah Akhlak teachers have an important role in shaping behaviour (behavioural) to be better and more conscious based on faith and piety and in fostering motivation to learn for students. This study aims to examine the role of Aqidah Akhlak teachers in increasing the learning motivation of broken home students at MTs Raudhatul Muttaqien Kalasan Yogyakarta. The research method used is a qualitative method with a qualitative descriptive approach. The data collection method uses observation, interviews, and documentation. The main subjects of this study are 1 Aqidah Akhlak teacher and six broken-home students. The results of this study indicate that: (1) The problems of broken home students at MTs consist of three aspects, namely psychological disorders, academic issues, and behavioural problems. (2) The learning outcomes of broken home students at MTs consist of three aspects: cognitive, affective and psychomotor. (3) The efforts of Aqidah Akhlak teachers in increasing the learning motivation of broken home students include providing advice, praise, and curiosity. (4) Internal and external factors are Supporting and inhibiting factors for Aqidah Akhlak teachers. The practical implications obtained by students with the motivation provided by Aqidah Akhlak teachers are increased learning in academic aspects and student behaviour.